Hypokalaemia with paralysis: don't forget the thyroid. (24th March 2011) - Catalano, Concetta; Caridi, Graziella; Postorino, Maria Concetta; Enia, Giuseppe
Abstract : The authors report the case of a 33-year-old Italian man who had three episodes of hypokalaemia with paralysis linked to hyperthyroidism. Because of its low prevalence in western populations, the diagnosis of thyrotoxic hypokalaemic periodic paralysis can be easily missed in non-Asian countries.